Impact of major duodenal papilla morphology on the outcomes of primary needle-knife fistulotomy for deep biliary cannulation - Amir Sadeghi; Erfan Arabpour; Reyhaneh Rastegar; Samareh Omidvari; Mehdi Azizmohammad Looha; Masoumeh Keshavarzian; Mohammad Reza Zali (Scientific Reports)
Abstract The morphology of the major duodenal papilla (MDP) plays a crucial role in the selection of the cannulation technique. Primary needle-knife fistulotomy (pNKF) is an advanced cannulation technique is getting more popular because of the lower risk of post-ERCP pancreatitis (PEP). However, few studies have explored the impact of MDP morphology on pNKF outcomes. This study aimed to assess the safety and efficacy of pNKF for different MDP morphologies. A review of medical records between 2022 and 2024 revealed 200 patients with naïve MDP who underwent pNKF at Taleghani Hospital. Patients were classified into the three groups on the basis MDP morphology: regular: n = 34 (17%), long: n = 104 (52%), and bulging: n = 64 (31%). There were no patients with small papilla who underwent pNKF in the records. We compared successful biliary cannulation, the difficulty of procedure, and post-ERCP adverse events among these three groups. The success rates of pNKF in primary biliary cannulation were 94.1%, 98.1%, and 98.4% in the patients with regular, long, and bulging papilla; respectively (p = 0.38). Moreover, there was no significant difference in the rates of PEP (p = 0.71), bleeding (p = 0.11), perforation (p = 0.48), or cholangitis (p = 1.00). However, the procedure in the regular papilla group was associated with more cannulation attempts (p = 0.025) and longer time for manipulation of the papilla (p < 0.001). In conclusion, pNKF is an effective and safe cannulation technique for regular, long, or bulging papillae, although it may be associated with more cannulation attempts and longer cannulation times for regular papilla. Further multicenter trials with large populations are needed to confirm these findings, and investigate the applicability and the outcomes of pNKF in small papillae.